Aeroelasticity in Turbomachines: Some Aspects of the Effect of Coupling Modeling and Blade Material Changes - François Moyroud; Georges Jacquet-Richardet; Torsten H. Fransson (International Journal of Rotating Machinery)
Two methods are generally used for the aeroelastic analysis of bladed-disc assemblies. The first, often referred to as the energy method, assumes that the fluid does not modify invacuum structural dynamic behavior. On the other hand, the second, based on an eigenvalue approach, considers the feedback effect of the fluid on the structure. In this paper, these methods are compared using different test cases, in order to highlight the limitations of the energy method. Within this comparison, the effect of material modifications on the coupled behavior of the assembly is examined.